The regulation of crypto exchanges providing stablecoin services in South Africa: Should they be regulated as banks? - Dyamond, Megan (Department of Commercial Law, 2025)
Crypto assets have been declared to be financial products in South Africa and crypto asset service providers (‘CASPs') are required to seek a licence under the Financial Advisory and Intermediary Services Act 37 of 2002 (‘FAIS Act') to provide advice or intermediary services in respect of stablecoins. Yet, certain events in the crypto asset industry in 2022 (namely, a global industry decline, bad practices, bankruptcies and fraud) raised the question of whether CASPs providing exchange services specifically in relation to stablecoins (‘stablecoin CASPs') should be regulated as banks, and subjected to more rigorous regulatory requirements than those applicable under the FAIS Act. This forms the basis of the research question in this dissertation. The research is qualitative in nature and considers certain aspects of existing legislation and scholarly opinions in investigating the research question. The dissertation uses the European Union's Markets in Crypto Assets Regulation of 2023 (‘MICAR') as a benchmark against which to consider the South African legal position. After examining relevant legislation and considering MICAR's position on crypto assets, the dissertation argues that it is not appropriate to regulate stablecoin CASPs as banks in South Africa. However, the dissertation also finds that, in certain instances, some stablecoin CASPs may have to register as banks, based on the activities that they conduct. The dissertation also identifies certain significant gaps in the existing framework applicable to stablecoin CASPs as financial services providers. It is recommended that, in order to protect vulnerable consumers, a unified regulatory framework should be developed to apply particular standards to stablecoin CASPs; such standards are specifically tailored to stablecoins, and are not generic to traditional financial products. Looking beyond the research question posed, it is recommended that this framework should cover issuers of stablecoins in order to address the macroeconomic risks that they pose. The dissertation concludes that further research is needed to address other aspects of stablecoin CASP regulation that fall beyond the scope of this dissertation.